Kebijakan Pemerintah, Informasi Media Sosial, Dukungan Keluarga, dan Hubungannya terhadap Kesiapan Vaksinasi Covid-19 pada Ibu Nifas: Government Policy, Social Media Information, Family Support, and Their Relationship to Covid-19 Vaccination Readiness in Postpartum Women - Fitriani, Lia (Journal of Public Health Education, 2024)
Introduction: The Covid-19 vaccination for pregnant and lactating women uses three types of vaccines, namely the Pfizer and Moderna mRNA platform Covid-19 vaccines and the Sinovac virus inactivated platform vaccine, according to availability. Government policies, social media information, and family support are factors that influence the readiness for Covid-19 vaccination in postpartum mothers. Objectives:  This study aims to determine the relationship between government policies, social media information, and family support with readiness for Covid-19 vaccination in postpartum mothers at the Paninggilan Health Center. Method: Using descriptive analytics with a cross-sectional approach. The sampling technique in this study used total sampling, where the sample used was 64 respondents. The instrument used is using a questionnaire. Then the data were analyzed using univariate analysis and bivariate analysis through statistical chi-square tests. Result: The results showed that the relationship between government policy and Covid-19 vaccination readiness obtained a p-value of 0.004, social media information with Covid-19 vaccination readiness obtained a p-value of 0.000, and family support with Covid-19 vaccination readiness obtained a p-value of 0.000. Conclusion: There is a relationship between government policy variables, social media information, and family support with the readiness of covid-19 vaccination for postpartum mothers at the Paninggilan Health Center in 2022.